Combinatorial biosynthesis of novel gentamicin derivatives with nonsense mutation readthrough activity and low cytotoxicity - Yang, Lihua; Zhai, Hang; Tian, Tingting; Liu, Botong; Ni, Xianpu; Xia, Huanzhang (Frontiers in Pharmacology, 2025)
BackgroundAminoglycosides (AGs) are one of the initial classes of antibiotics that have been used clinically and possess broad spectrum of activity. Nevertheless, their clinical utilization is restricted by safety issues associated with nephrotoxicity and ototoxicity.MethodsGlycosyltransferase (GT) KanM2 was introduced into M. echinospora to produce the gentamicin derivatives, in which a kanosamine sugar ring was introduced to replace the garosamine. The premature termination codon (PTC) readthrough activity of genkamicins (GKs) was compared using dual luciferase reporter assay. The toxicity of GK was assessed in vitro in HEK-293 and NCI-H1299 cells and determined based on cell viability calculated after 48 h of treatment with different concentrations of the compounds. The NCI-H1299 cells harbouring the R213X nonsense mutation were treated with different concentrations of the derivatives to compare their expression of p53 proteins. The expression of p53 and its downstream targets p21 and BAX was detected using Western blotting and qRT-PCR in NCI-H1299 cells containing the R213X nonsense mutation treated with different concentrations of GK-Ae and G418. Finally, immunofluorescence and flow cytometry were used to determine the subcellular localization of full-length p53 protein induced by GK-Ae treatment and its effect on apoptosis in cancer cells.ResultsEight gentamicin derivatives were obtained in this study. GK-Ae displayed similar PTC readthrough activity and reduced toxicity compared to natural aminoglycoside G418. Moreover, GK-Ae increased the levels of both p53 and its downstream targets p21 and BAX, and promoted apoptosis of cancer cells.ConclusionThese results demonstrate the potential of combinatorial biosynthesis to increase the diversity of structures of AGs and provide directions for the development of new AGs with low toxicity and high PTC readthrough activity.